The association between body mass index and risk of preoperative oxygenation impairment in patients with the acute aortic syndrome - Zhang, Chiyuan; Shi, Ruizheng; Zhang, Guogang; Bai, Hui; Zhang, Yanfeng; Zhang, Lei; Chen, Xuliang; Fu, Zuli; Lin, Guoqiang; Xu, Qian (Frontiers in Endocrinology, 2022)
Objective: The study aimed to determine the relationship between body mass index (BMI) and the risk of acute aortic syndrome (AAS) with preoperative oxygenation impairment. Methods: A meta-analysis of published observational studies involving BMI and AAS with preoperative oxygenation impairment was conducted. A total of 230 patients with AAS were enrolled for retrospective analysis. All patients were divided into 2 groups (Non-oxygenation impairment group and Oxygenation impairment group). Logistic regression analysis was performed to assess the relation between BMI and the risk of preoperative oxygenation impairment after the onset of AAS. Dose-response relationship curve and subgroup analysis were conducted to test the reliability of BMI as an independent factor of it. Results: For the meta-analysis, the quantitative synthesis indicated that excessive BMI increased the risk of preoperative oxygenation impairment (OR: 1.30, 95% CI: 1.05-1.60, Pheterogeneity = 0.001). For the retrospective analysis, a significant association was observed after adjusting for a series of variables. BMI was significantly related to preoperative oxygenation impairment after the onset of AAS (OR: 1.34, 95% CI: 1.15-1.56, p <0.001), and compared with normal weight group (18.5 kg/m2 ≤ BMI < 23.0 kg/m2), the individuals with excessive BMI were at higher risk of preoperative oxygenation impairment for the obese group (BMI ≥ 25 kg/m2) (OR: 17.32, 95% CI: 4.03-74.48, p <0.001). A J-shape curve in dose-response relationship analysis further confirmed their positive correlation. Subgroup analysis showed that diastolic blood pressure (DBP) ≥ 90mmHg carried an excess risk of preoperative oxygenation impairment in obese patients. Conclusion: Excessive BMI was an independent risk factor for AAS with preoperative oxygenation impairment.